2002
DOI: 10.1094/pdis.2002.86.10.1163
|View full text |Cite
|
Sign up to set email alerts
|

Potato Late Blight Management in the Toluca Valley: Field Validation of SimCast Modified for Cultivars with High Field Resistance

Abstract: Management of potato late blight in the highland tropics is very costly and remains difficult. Reducing the impact of late blight through the use of resistant cultivars in combination with a fungicide forecasting system could lower the number of costly fungicide applications. Previously, we evaluated the fungicide advisory SimCast for use with Mexican cultivars of high levels of field resistance for use in the central highlands of Mexico and found that it predicted too many fungicide applications for cultivars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 12 publications
0
24
0
1
Order By: Relevance
“…The form of SimCast (Grü nwald et al 2002) suggested a simple linear model would not be sufficient. We developed and tested GAMs to model the relationship between aggregated weather data and aggregated 'true' blight units (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The form of SimCast (Grü nwald et al 2002) suggested a simple linear model would not be sufficient. We developed and tested GAMs to model the relationship between aggregated weather data and aggregated 'true' blight units (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…3) (Fig. 3) that might reasonably be expected based on the structure of SimCast (Grü nwald et al 2002). Once the metamodel forms were selected, metamodels for resistant genotypes were also constructed using these forms of GAM for mm Daily resistant and mm Monthly resistant (Fig.…”
Section: Metamodel Construction and Fitmentioning
confidence: 99%
See 2 more Smart Citations
“…Disease forecasting models demand a permanent need of validation due to continuous modifications in the model (Andrade-Piedra et al, 2005). The method of validation is to test the model fitness within its region of application and consistent with its future aspects (Grünwald et al, 2002). A disease predictive model may reduce uncertainty about the management decisions by providing a quantitative description of disease potential.…”
Section: Introductionmentioning
confidence: 99%